Leitura literária e o ensino de Língua Portuguesa no Ensino Fundamental – 6º ao 9º ano: margens opostas ou travessia? - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2020)
This Dissertation entitled Literary reading and the teaching of Portuguese in Elementary School - 6th to 9th grade: opposite margins or crossing? arises from a pedagogical need - literary education - so he investigated where Literature is in Portuguese Language classes. For data collection, comparisons, analysis of results, intervention and discussion, a semi-structured questionnaire was applied, with closed and opened questions to eight (08) Portuguese language teachers and two hundred and five students (205). The research was carried out in (05) five schools of the State Public Network, in the municipality of Santarém-PA. As an important part of the investigation, there was the verification and enumeration of the occurrence of literary texts in Portuguese language textbooks, used by students and teachers from those schools, in order to verify whether this pedagogical instrument promotes literary education through your texts. The data obtained with the application of the questionnaire were important for the realization of the intervention proposal, as they were socialized with the teachers participating in the research, in a scheduled meeting where several questions were asked, among which the absence of methodologies, collective planning and of Portuguese Language training courses for teaching Literature in Elementary Education, in addition to discussions aimed at developing strategies, capable of giving the literary text the potential it has. The bases used were Cândido (2004), Cosson (2012), Silva (1991,2004, 2009), Zilberman (2009), Geraldi (2012), in addition to articles and dissertations that dialogue with this theme. The analysis of the results obtained reveals that, although the literary text is linked to the teaching of the Portuguese language, it has only been the pretext for the teaching of normative grammar, for solving questions of comprehension and interpretation of texts, as well as a model for writing of texts of the same genre, thus not promoting literary education. Thus, an E-book was created, entitled “Invitation to crossing”, as a suggestion to Portuguese teachers of elementary school - 6th to 9th grade - in order to make not only present, but continuous and provocative the teaching of Literature in Portuguese language classes, being able to hold the student's attention and, thus, promote literary education, becoming a less didactic and more humanizing practice.
Keywords: Língua Portuguesa; Educação Literária; Literatura.; Livro Didático; CNPQ::CIÊNCIAS HUMANAS; LINGUAGENS, LEITURA E EDUCAÇÃO; LINGUAGENS E LETRAMENTOS